An Experimental Act: Formations of Wildness and Indigeneity in Far North Queensland. Issue 3 (2nd July 2016) - Neale, Timothy
Abstract : In this article, I focus upon the recent Wild Rivers Act controversy in Queensland, Australia, as an 'experimental event' that drew together a diverse cast of actors – including Indigenous traditional owners, state politicians, bureaucrats, environmentalists, mining companies, the late Steve Irwin, and waterways – to contest the future of a region historically (over)coded as 'wild'. In attending to these actors, and the discourses and arguments mobilised, I argue that this controversy reveals emergent trends in the imaginaries of wildness and indigeneity surrounding indigenous lands and waters in contemporary settler colonial nations. Critical insight into such issues, I show, requires reconceptualising the static 'matters of being' through which indigenous territory is often captured – such as tradition and development – as contingent and contested 'matters of becoming'. It is precisely in events such as the Act controversy that the contemporary politics of indigenous territory, and its contingent and contested foundations, becomes visible.